A better understanding of ambulance personnel's attitude towards real-time resuscitation feedback. (11th January 2018) - Brinkrolf, Peter; Lukas, Roman; Harding, Ulf; Thies, Sebastian; Gerss, Joachim; Van Aken, Hugo; Lemke, Hans; Schniedermeier, Udo; Bohn, Andreas
Abstract: Objective: High-quality chest compressions during cardiopulmonary resuscitation (CPR) play a significant role in surviving cardiac arrest. Chest-compression quality can be measured and corrected by real-time CPR feedback devices, which are not yet commonly used. This article looks at the acceptance of such systems in comparison of equipped and unequipped personnel. Design: Two groups of emergency medical services' (EMS) personnel were interviewed using standardized questionnaires. Setting: The survey was conducted in the German cities Dortmund and Münster. Participants: Overall, 205 persons participated in the survey: 103 paramedics and emergency physicians from the Dortmund fire service and 102 personnel from the Münster service. Intervention: The staff of the Dortmund service were not equipped with real-time feedback systems. The test group of equipped personnel of the ambulance service of Münster Fire brigade uses real-time feedback systems since 2007. Main outcome measure: What is the acceptance level of real-time feedback systems? Are there differences between equipped and unequipped personnel? Results: The total sample is receptive towards real-time feedback systems. More than 80% deem the system useful. However, this study revealed concerns and prejudices by unequipped personnel. Negative ratings are significantly lower at the Münster site that is experienced with the use of the real-time feedback system in contrast to the Dortmund site where no such experience exists—the system's use in daily routine results in better evaluation than the expectations of unequipped personnel. Conclusions: Real-time feedback systems receive overall positive ratings. Prejudices and concerns seem to decrease with continued use of the system.